EVALUATION OF INNOVATIVE PROJECTS IN CONTROLLING SYSTEM - Vladimir P. Bogko; Alexandr M. Batkovsky; Mikhail A. Batkovsky; Sergey I. Bokov; Alexandr N. Stiazkin (Статистика и экономика)
Implementation of the controlling system onto the high-tech enterprises requires the development of specific tools for their evaluation. The models of projects estimation are offered on the article on the basis of the methods of factor analysis, linear regression analysis and fuzzy logic of Mamdani’s algorithm.